Evaluasi Pembelajaran Anak Usia Dini - Aili Erisa; Ghina Yunita; Silvia Ramadhani Arsa; Nurul Aulia Kuswari Lubis; Nala Muthia; Ampun Bantali (STAI AL-AMIN, 2026)
This study aims to describe the implementation of early childhood learning evaluation through a literature review of books, scholarly articles, and official PAUD assessment guidelines. The findings indicate that effective evaluation must utilize authentic assessment methods such as observation, anecdotal records, portfolios, and performance assessments to obtain a comprehensive picture of children's development. However, its implementation still faces several challenges, including teachers’ administrative workload, limited evaluation competence, parents’ perceptions that are not aligned with PAUD principles, non-standardized assessment instruments, and insufficient time for proper observation. This study emphasizes the need for improved teacher training, streamlined administrative processes, and strengthened collaboration with parents to ensure that PAUD learning evaluation becomes more optimal and development-oriented.